2010
DOI: 10.1021/ol902675k
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis of tert-Allylic Ethers via Gold(I)-Catalyzed Intermolecular Hydroalkoxylation of Allenes

Abstract: A highly regioselective method towards tertiary allylic ethers via gold(I)-catalyzed intermolecular hydroalkoxylation of allenes is disclosed. Preventing subsequent isomerization of the tertiary allylic ether products to primary allylic ethers appears to be the key to achieving high regioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…While protodeauration of the gold catalyst is conventionally depicted as an irreversible process in a catalytic reaction, Lee recently reported an example of reversible hydroalkoxylation23 in the presence of Ph 3 PAuNTf 2 . Furthermore, an irreversible reaction under catalytic conditions would allow us to exclude the possibility that the incomplete chirality transfer we observed previously was due to racemization of the product.…”
Section: Resultsmentioning
confidence: 99%
“…While protodeauration of the gold catalyst is conventionally depicted as an irreversible process in a catalytic reaction, Lee recently reported an example of reversible hydroalkoxylation23 in the presence of Ph 3 PAuNTf 2 . Furthermore, an irreversible reaction under catalytic conditions would allow us to exclude the possibility that the incomplete chirality transfer we observed previously was due to racemization of the product.…”
Section: Resultsmentioning
confidence: 99%
“…If the quantity of EtOH was reduced (1 equiv) a 2:1 mixture of the corresponding regioisomeric allylic ethers 9a and 9’a was obtained, however, the addition of a protic additive [ t -BuOH (5 equiv)] restored the high regioselectivity (>99:1) [1819]. Lee and Hadfield demonstrated that the use of an excess of methanol retarded the isomerization of the tertiary allylic ether 9b into the primary allylic isomer 9’b , which is also catalyzed by the gold complex [29] (Scheme 8). The isomerization was also found to be catalyst dependent and did not operate in the presence of the NHC–gold complex [(IPr)AuOTf].…”
Section: Reviewmentioning
confidence: 99%
“…Thus, when cyclopropene 8 was treated with a stoichiometric quantity of EtOH in the presence of the latter catalyst (5 mol %), the tertiary allylic ether 9a was obtained with high regioselectivity (>99:1), but the yield (51%) was not as high as with Gagosz’s catalyst (83%). Lee and Hadfield took advantage of these findings to develop the regioselective addition of alcohols (used in excess) to allenes such as 14 catalyzed by [(IPr)AuOTf] (10 mol %) to produce the tert -allylic ethers 15 as the kinetic products (Scheme 8) [29]. …”
Section: Reviewmentioning
confidence: 99%
“…Following these seminal reports, Paton and Maseras proposed, based on DFT calculations, that the regioselectivity observed by Widenhoefer and Yamamoto is due to isomerisation of the kinetic tertiary allylic ether 3 to the thermodynamic primary allylic ether 2 , rather than preferential activation of 1 at the less‐hindered double bond, as originally assumed (reaction (2), Scheme ) . Drawing on previous success in controlling the regioselectivity of gold‐catalysed alcohol additions to cyclopropenes, we subsequently developed conditions to suppress isomerisation of 3 to 2 , thereby switching the regioselectivity to the kinetic, tertiary allylic ether product 3 (reaction (3), Scheme ) . The use of DMF as solvent was the crucial difference, possibly because it reduces the activity of the active cationic gold catalyst (IPr)Au + (IPr=1,3‐bis(2,6‐diisopropylphenyl)imidazol‐2‐ylidene) by means of reversible coordination …”
Section: Introductionmentioning
confidence: 97%
“…[13] Drawing on previous success in controlling the regioselectivity of gold-catalysed alcohola dditions to cyclopropenes, [14] we subsequently developed conditions to suppress isomerisation of 3 to 2,t hereby switching the regioselectivity to the kinetic, tertiarya llylic ether product 3 (reaction (3), Scheme 1). [15] The use of DMF as solvent was the crucial difference, possibly because it reduces the activity of the active cationic gold catalyst( IPr)Au + (IPr = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene) by means of reversible coordination. [16] In contrast to 1-substituted and 1,1-disubstituted allenes 1, 1,3-disubstituted allenes 4 have been far less studied,p resumably due to regioselectivity issues when R 1 and R 2 are not electronically differentiated.…”
Section: Introductionmentioning
confidence: 99%